Waqf and the sustainable development goals: examining the pathways of governance and resource utilization in Indonesia - Ade Sofyan Mulazid; Yoghi Citra Pratama; M. Arskal Salim GP; Wahdi Sayuti; Yessi Fitri; Muhaimin Muhaimin; M. Syukri (Jurnal Konseling dan Pendidikan, 2026)
Waqf is an important instrument in Islamic social finance with significant potential to support the achievement of the Sustainable Development Goals (SDGs), particularly in developing countries such as Indonesia. However, the contribution of waqf to sustainable development largely depends on the quality of governance and the effective utilization of waqf assets. This study aims to examine the influence of waqf governance and waqf utilization on the achievement of the SDGs in Indonesia, as well as to analyze their mediating role in the relationship between waqf resources and sustainable development outcomes. This research adopts a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from waqf management institutions and relevant stakeholders in Indonesia. The results indicate that waqf governance has a positive effect on SDG achievement (β = 0.2644), while waqf utilization shows a stronger positive influence (β = 0.4958). Furthermore, waqf resources positively affect both governance and utilization. These findings highlight the importance of strengthening governance practices and optimizing the utilization of waqf assets to enhance the contribution of Islamic social finance to sustainable development.